1985
DOI: 10.1111/j.1365-3024.1985.tb00474.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of host serum on feeding by Trichostrongylus colubriformis (nematoda)

Abstract: The effect of host serum on in vitro feeding by Trichostrongylus colubriformis was studied by incubating adult helminths in goat serum containing the dye, Rhodamine B. The amount of dye ingested was determined by fluorometric analysis. Immune serum from goats infected with T. colubriformis suppressed helminth feeding, while normal serum from uninfected goats did not. Suppression of feeding by immune serum increased with the duration of the host's infection. Heat-inactivation (56 degrees C) of immune serum did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…High IgG levels were associated with reduced worm infection in immunized (Harrison et al, 2008) and genetically resistant sheep (Gill, 1991;Pernthaner et al, 2006). The protective activity of IgG was attributed to neutralizing metabolic enzymes (Smith et al, 1985) and suppressing the ability of the worms to feed (Bottjer et al, 1985).…”
Section: Antibody Responsementioning
confidence: 98%
“…High IgG levels were associated with reduced worm infection in immunized (Harrison et al, 2008) and genetically resistant sheep (Gill, 1991;Pernthaner et al, 2006). The protective activity of IgG was attributed to neutralizing metabolic enzymes (Smith et al, 1985) and suppressing the ability of the worms to feed (Bottjer et al, 1985).…”
Section: Antibody Responsementioning
confidence: 98%
“…Furthermore, the smaller size of the worms recovered from resistant sheep ( Figure 2) might suggest that anti-parasite IgA and lgGl antibodies contribute to resistance by neutralizing/inactivating vital metabolic enzymes thus compromising the metabolism, growth, reproductive capacity or mobility of the parasite. Antiparasite IgGl has been shown to suppress Trichostrongylus colubriformis feeding in vitro (Bottjer, Klesius & Bone 1985) and it has been reported that IgA may retard the growth of Ostertugiu in a dose-dependent manner in immune sheep (Smith et al 1985). In addition, IgG antibodies in association with mucus have been shown to significantly reduce the establishment of infective larvae in immune hosts (Carlisle, McGregor & Appelton 1990).…”
Section: Parasite Immunologymentioning
confidence: 99%
“…The role of serum and intestinal antibodies in conferring protective immunity against T. colubriformis remains obscure. However, serum from sheep immunised against T. colubriformis has reduced the in vitro feeding and oviposition of the nematode (Bottjer et al 1985;Bone and Klesius 1986). Transfer of passive immunity via immune sheep or guinea-pig serum against T. colubriformis (Connan 1972;Ross and Halliday 1982) or immune sheep serum against T. axei (Ross and Halliday 1979) has also been demonstrated to induce protection against homologous challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies secreted into the intestine may bind to the nematode molecules (Douch et al 1996) and interfere with nematode feeding (Bottjer et al 1985) and oviposition (Bone and Klesius 1986). For a thorough understanding of the host immune response and the mechanism of parasite survival it would be desirable that initial studies be carried out on suitable laboratory-model animals (Bezubik et al 1988).…”
Section: Introductionmentioning
confidence: 99%